The infrastructure development success model for public-private partnership in UAE - Rashed Salem Alkaabi, Rashed Juma (2022)
Public private partnerships (PPPs) have been used internationally as a strategy to develop infrastructure projects. In general, an expanded usage of the PPP strategy can be clarified in terms of its planned advantages such as exposure to private financing for program expansion; effective control and distribution of risk; simpler project targets; new concepts and flexibility; enhanced tendering preparation and incentives; and greater value for money (VfM) for public initiatives. In the last couple of decades, PPP has become a major approach in delivering infrastructure projects. The United Arab Emirates (UAE) in the Gulf Cooperation Council (GCC) countries was the largest market for public-private partnerships in the last decade. PPPs are currently used more and more for the rapid evolution of the UAE projects for infrastructure. However, the success factors for adopting a similar approach for infrastructure projects in the UAE are not widely understood. The objective of this research is to identify, assess and evaluate the impact of PPP formula factors and the development of infrastructure in UAE. A questionnaire survey was carried out among experts working in government institutions in Abu Dhabi in UAE. A total of 295 questionnaires were collected and found valid. Analysis of Moment Structural Equation Modelling (AMOS-SEM) model was developed based on 5 groups related to the important factors of formulation factors of PPP which are: Trust; Formulation of PPP; Transparency; Governance; and success of infrastructure development. The findings from the important Formulation factors of PPP through path analysis using structural model indicate that the critical Formulation factors of PPP have a significant effect on infrastructure development success. The implication of this research is that decision and policy makers can enhance and further strengthen PPP through focusing on trust, formulation of PPP and transparency to enhance the success of infrastructure development.